IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH DASAR NEGERI 51 BANDA ACEH - kartika, pia ade; Husin, M.; Safiah, Intan (Universitas Syiah Kuala, 2024)
The aim of this research is, to describe the implementation of the school literacy program at SD Negeri 51 Banda Aceh and the supporting and inhibiting factors for implementing the school literacy movement program at SD Negeri 51 Banda Aceh. The approach used in this research is a qualitative descriptive research type approach. The research subjects were the principal, class teacher and class VI students at SDN 51 Banda Aceh. Data collection techniques in this research are observation, interviews and documentation. Meanwhile, data analysis techniques use data collection, data reduction, data presentation, and data conclusions. The results of the research show that the implementation of the School Literacy Movement at SDN 51 Banda Aceh was carried out based on the habituation stage, development stage and learning stage. The supporting factors at SDN 51 Banda Aceh are in the form of libraries, reading books, magazines and reading corners. There are also inhibiting factors, such as students' poor reading habits and libraries that are not running well because there is no special staff to manage the library..